2000
DOI: 10.1515/bc.2000.153
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein Photobleaching: a Model for Protein Damage by Endogenous and Exogenous Singlet Oxygen

Abstract: Characterization of protein damage during photosensitization of chlorin e6-treated cells was performed using the green fluorescent protein (GFP). The GFP-chromophore damage caused by singlet oxygen was studied in COS 7 kidney cells and E. coli bacteria following light irradiation. Electron spin resonance (ESR) revealed the generation of endogenous singlet oxygen (1O2) by photoactivated GFP, an effect similar to that produced by the exogenous photosensitizer chlorin e6. A light dose-dependent photobleaching eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 29 publications
8
92
2
Order By: Relevance
“…8). A major role of 1 O 2 in this is indicated by the inhibition of GFP fluorescence bleaching by azide (22). Crucial residues for fluorescence of GFP (9,31) and catalytic function of NEO (19) may be modified by this ROS in the uroporphyric cells, accounting for their loss of these activities, as reported for several functional proteins in solution (11,18).…”
Section: Discussionmentioning
confidence: 95%
“…8). A major role of 1 O 2 in this is indicated by the inhibition of GFP fluorescence bleaching by azide (22). Crucial residues for fluorescence of GFP (9,31) and catalytic function of NEO (19) may be modified by this ROS in the uroporphyric cells, accounting for their loss of these activities, as reported for several functional proteins in solution (11,18).…”
Section: Discussionmentioning
confidence: 95%
“…5 D and G). Because photobleaching and ROS generation are parallel biophysical processes, this rapid photobleaching indicates that ROS are generated very quickly in this setting (25). This 15-s irradiation time was sufficient to inactivate FKBP12(F36V)-␤-gal (Fig.…”
Section: A Fluorescent Conjugate Of the Fkbp12(f36v) Ligand Slfmentioning
confidence: 96%
“…It has been shown that excited fluorophores interact with dissolved oxygen producing reactive oxygen species, such as super oxide radicals (Wright et al, 2002). These can oxidize and destroy a variety of components, such as proteins and their associated fluorophores, leading to a loss of fluorescence signal (Greenbaum et al, 2000;Bernas et al, 2004). For this to happen, oxygen must collide with the excited dye.…”
Section: Applications For Low-temperature Gfp Imaging With Reduced Phmentioning
confidence: 99%